Writing for Publication in Informatics and Data Science in Clinical Research - Ittenbach, Richard; Ittenbach, William A (Journal of the Society for Clinical Data Management, 2021)
Clinical data management and its contemporary analogs, clinical research informatics and clinical data science constitute a small but rapidly growing specialty within the broader field of biomedical science. As such, the literature base is just evolving, drawing heavily from the larger and more established disciplines of biomedical informatics, biostatistics, clinical operations, and regulatory affairs. The purpose of this paper is to offer suggestions to individuals interested in submitting their research to the Journal of the Society for Clinical Data Management: Informatics and Data Science in Clinical Research.